Let me out = Let mi aut [videorecording (DVD)] - Kim, Chang Lae; Soh, Jae; Kwon, Hyun-Sang; Park, Hee Von; Choi, Jessica (Giant Ape Media, 2014)
Eternal senior Mu-Young is a film student who's seen every movie you haven't and thinks your favorite director is a hack. He's happy to churn out criticism until a famous indie filmmaker funds his unproduced zombie masterpiece and gives the amateur auteur the chance to prove he's the next big thing in Korean cinema. On the set, melodrama quickly bleeds out of the script and into the shoot. Mu-Young's undead are underwhelming, the star's a total diva, and the cast and crew are one step away from mutiny.